Is Sonographic Assessment of Intratendinous Blood Flow in Achilles Tendinopathy Patients Reliable? - Risch, L.; Cassel, M.; Messerschmidt, J.; Intziegianni, K.; Fröhlich, K.; Kopinski, S.; Mayer, F. (Ultrasound International Open, 2016)
The purpose of this study was to investigate the consistency between different Doppler ultrasound (DU) modes as well as the intra- and inter-observer reliability of investigators with different experience level in assessing intratendinous blood flow (IBF) in Achilles tendinopathy patients. 18 participants (36 Achilles tendons, AT) with Achilles tendinopathy (24 AT) were examined with power Doppler ultrasound (PDU), colour Doppler ultrasound (CDU) and “Advanced Dynamic Flow” (ADF) (Toshiba Xario SSA-660 A; 14MHz transducer) by 2 investigators (experienced, EI; inexperienced, II) in a test-retest design (M1/M2). A modified Öhberg score was used to quantify IBF. Data was analysed descriptively (absolute and relative). Consistency of the 3 modes was presented by Kendall’s Coefficient of Concordance (Kendall’s W). Intra- and inter-observer reliability were calculated by use of Kendall’s tau b correlation coefficient.IBF was detected in 79–92% of symptomatic AT and in 33–50% of contralateral asymptomatic AT. Comparing the 3 modes, Kendall’s W ranged from 0.97–0.98. Analysis of intra-observer reliability resulted in Kendall’s tau 0.90–0.92 for EI and 0.84–0.87 for II. Inter-observer reliability resulted in Kendall’s tau 0.64–0.69 in M1 and 0.68–0.70 in M2.The very good consistency between PDU, CDU and ADF indicates a comparable applicability for assessing IBF in ATs. Intra-observer reliability was high for both investigators, independent of experience. The moderate inter-observer reliability reflects the challenge in sonographic detection of intratendinous blood flow (IBF) amount.
Keywords: ultrasound-power doppler; ultrasound-color doppler; advanced dynamic flow; achilles tendon; reliability